Advances in Nano-Scale Plugging Agents for Water-Based Drilling Fluids: Mechanisms and Applications (International Journal of Scientific Research and Management (IJSRM), 2025)
During drilling operations, the efficient sealing of nano- to micro-scale fractures effectively mitigates the invasion of the fluid phase, ensures the long-term structural stability of shale formations, and suppresses hydration swelling together with associated wellbore-instability phenomena. Consequently, determining how to seal nano- and micro-scale fractures in shale reservoirs has become a prominent and intensively studied topic within the domain of water-based drilling-fluid research. Nano-sealing materials, characterized by their ultra-fine particle dimensions together with their distinctive physical and chemical properties, demonstrate pronounced potential for improving fluid-loss control as well as for enhancing overall wellbore stability. Building upon this foundation, the present study systematically classifies the nano-plugging agents that have been reported in recent years, conducts a detailed analysis of their respective sealing mechanisms, and explores the prospective developmental trajectories of nano-plugging agents, thereby offering new and valuable insights for subsequent investigations focused on water-based drilling-fluid plugging agents. Nano-emulsion plugging agents possess multifunctional, high-efficiency, low-cost, safe, and environmentally friendly characteristics, and the related research holds substantial engineering significance and practical value.